Human NF-κB1 Haploinsufficiency and Epstein–Barr Virus-Induced Disease—Molecular Mechanisms and Consequences - Hoeger, Birgit; Serwas, Nina Kathrin; Boztug, Kaan (Frontiers in Immunology, 2018)
Nuclear factor kappa-light-chain enhancer of activated B cells 1 (NF-kB1)-related human primary immune deficiencies have initially been characterized as defining a subgroup of common variable immunodeficiencies (CVID), representing intrinsic B-cell disorders with antibody deficiency and recurrent infections of various kind. Recent evidence indicates that NF-kB1 haploinsufficiency underlies a variable type of combined immunodeficiency (CID) affecting both B and T lymphocyte compartments, with a broadened spectrum of disease manifestations including Epstein-Barr virus (EBV)-induced lymphoproliferative disease and immediate life-threatening consequences. As part of this review series focused on EBV-related primary immunodeficiencies, we discuss the current clinical and molecular understanding of monoallelic NFKB1 germline mutations with special focus on the emerging context of EBV-associated disease. We outline mechanistic implications of dysfunctional NF-kB1 in B and T cells, and discuss the fatal relation of impaired T-cell function with the inability to clear EBV infections. Finally, we compare common and suggested treatment angles in the context of this complex disease.